2016
DOI: 10.1007/978-3-319-44817-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Refactoring Software Development Process Terminology Through the Use of Ontology

Abstract: Abstract. In work that is ongoing, the authors are examining the extent of software development process terminology drift. Initial findings suggest there is a degree of term confusion, with the mapping of concepts to terms lacking precision in some instances. Ontologies are concerned with identifying the concepts of relevance to a field of endeavour and mapping those concepts to terms such that term confusion is reduced. In this paper, we discuss how ontologies are developed. We also identify various sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…It is well documented that software development is a complex socio-technical activity [42], the process for which needs to be vigilantly maintained and evolved [43]. We furthermore find that roles within software development can have varying names [44], and that the very terminology adopted is perhaps the source of some fusion [45] [46]. We have also seen that the process and the details of work carried out when producing software are also variable given any particular development setting [47] [48].…”
Section: Introductionmentioning
confidence: 63%
“…It is well documented that software development is a complex socio-technical activity [42], the process for which needs to be vigilantly maintained and evolved [43]. We furthermore find that roles within software development can have varying names [44], and that the very terminology adopted is perhaps the source of some fusion [45] [46]. We have also seen that the process and the details of work carried out when producing software are also variable given any particular development setting [47] [48].…”
Section: Introductionmentioning
confidence: 63%
“…A final point we wish to acknowledge relates to the terminology we have chosen to describe the approach we have presented in this paper: CSE. As Georg Hegel, the German Philosopher who offered valuable insights on language, observed “truth is found neither in the thesis nor the antithesis, but in an emergent synthesis which reconciles the two.” Indeed, in other research, the authors have argued that inconsistency in relation to software process terminology application may be a somewhat underappreciated concern at this time . Thus, there are contemporary implications for our application of the word continuous .…”
Section: Discussionmentioning
confidence: 97%
“…And this task of researching the available process alternatives must be frustrated by the fragmented process terminology, where in previous basic research we have found that individual concepts can be branded using many different terms [30][31]. Yet ironically, an absence of attention to the various available techniques could be damaging to the success of any given firm.…”
Section: Discussionmentioning
confidence: 99%
“…), Systems, Software and Services Process Improvement: 24th European Conference, EuroSPI 2017, Ostrava, Czech Republic, , Proceedings (pp. [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Cham: Springer International Publishing.…”
Section: Introductionmentioning
confidence: 99%